(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article presents ideas and comments on the competence of directors of general secondary educational institutions to manage competition, its analysis in the conditions of the education system of Uzbekistan, strategic and innovative components, the competitive environment, and priority areas for the development of competence in managing competition.